Konglanjo - Bongasu-Tanla-Kishani (Book collections on Project MUSE., 2010)
This collection of poems evolves as a network and satellite of an expressive pursuit of justice with a difference. For, though this poetry simultaneously shapes global and grassroots smiles and tears, its corpus is no matter for laughter or weeping. In familiar but not identical voices, the poet tackles social evils as parasites while cross-examining cultural assumptions in the same vein. Triple form-title poem, Letters to Ethiopia and Some Random poems, explores nightmares of colonial mission civilisatrice by dint of two decades of inspirational events from 1965 as invitations into a more serene world emerging from post-discoveries. --Book Jacket.